PERLINDUNGAN HUKUM PIDANA TERHADAP PEMBERI HAK TANGGUNGAN YANG BUKAN DEBITUR - Saladin, Tomi (IAIN Syekh Nurjati Cirebon, 2019)
In the practice of the credit agreement with the guarantee of the right of liability by the bank as creditors, then if debtor tort in carrying out the payment of the debt to the creditor, then the creditor has the right to execute The object of the rights of liability with its own power after first requesting for Fiat Yustitsia from the state court chairman where the land is located. In the case of an auction dispute execution of the object guarantees rights between Bank Danamon as the creditor with Zn as debtor, Bank Danamon as the creditor declared to have violated the provisions of the law in executing the object of the rights assurance of debtor Zn. But in the fact that execution or auction execution of the object of guarantee of the rights of liability has been in accordance with the provisions of article 6 and article 20 UUHT No. 4 year 1996 and also has been in accordance with the provisions and procedures of Procedure execution auction Rights Assurance object under the auction law. The problem discussed in this study is how the legality and legal force of the Auction object guarantees the rights of the liability of the obligation carried out on the application of the creditor holders of the certificate.Â Â